Owl diaries : eva and the new owl - Elliott, Rebecca (New York : Scholastic, 2016)
There is a new owl in Treetopolis! Her name is Hailey. Eva really wants Hailey to be her friend, but Hailey doesn't seem to want to spend time with Eva. Then Hailey starts hanging out with Eva's best friend, Lucy! Will Eva lose her most flap-tastic friend?